The formalism of the formal mortgage contract a study in Iraqi law - Ghani Abul-Hussien, Rusol; Hassan Bshat AlSaeedy, Jaleel (International Journal of Psychosocial Rehabilitation, 2020)
The formal mortgage is one of the most important tools of credit, which has benefits for the mortgagor, the mortgagee and third parties. Therefore, the legislator considered it a deed contract, for the mortgagor remains the owner of the mortgaged property In order to obtain the loan amount that he needs, For the mortgagee, as providing the loan to the mortgagor is secured by the mortgaged property. For third parties, the formality of the mortgage makes the third party aware of the existence of the mortgage and is not deceived by the fact of the debtor's financial position. Iraqi law has derived it from Roman law, Which was known as the mortgage, which is decided by agreement of the parties without taking into account the official procedures. And the legal mortgage decided by the provision of law for the minor in the trustee's money and the wife in her husband's money, It was subject matter in both real property and personal property. Then it passed to French law in the thirteenth century, but restricted it to real property. it was approved by the Napoleonic law of three types of mortgages: the mortgage by agreement is required in the formal; the legal mortgage, in which the publicity is not required; with the and of the judicial mortgage, which is decided by the force of law according to the decision of the judiciary. this mortgage system was entered in Iraq for the first time by a law issued by the Ottoman Empire. Is the law of immovable property documenting debt, Issued on February 25, 1910, Its provisions were inspired by French law. Until the issuance of the Iraqi Civil Law in 1951, which abolished the advanced law, the latter regulated the provisions of the formal mortgage, including the formality of the mortgage, in Articles 1285-1320. The legislator has quoted most of its provisions from the Egyptian Civil Law, a little immovable property law documenting debt, but restricted mortgages by agreement only.